Amino-functionalization on graphene oxide sheets using an atomic layer amidation technique. Issue 2 (12th December 2019) - Gu, Siyong; Hsieh, Chien-Te; Mallick, Bikash Chandra; Ashraf Gandomi, Yasser; Chang, Jeng-Kuei; Li, Jianlin; Liaw, Peter K.
Abstract : Nitrogen functionalization on graphene sheets has solely been demonstrated with a stepwise amidation implementation within the literature. Abstract : Nitrogen functionalization on graphene sheets has solely been demonstrated with a stepwise amidation implementation within the literature. The present work proposes an atomic layer amidation (ALN) technique to linearly adjust the surface amidation level on the carbon nanostructures. The ALN cycling protocol proposed in this work consists of an ammonia pulse, nitrogen pulse, and pumping at 100 and 150 °C. Both surface amidation and oxidation levels were linearly controlled by the ALN cycle number. The ALN technique was demonstrated as a self-limiting process capable of step-by-step N-functionalizing graphene oxide (GO) sheets on the atomic scale. The amidation reaction rates were ca. 0.023 (100 °C) and 0.028 atomic percent (at%) cycle −1 (150 °C), and the apparent activation energy was determined to be 14.3 kJ mol −1 (= 0.148 eV atom −1 ) from the Arrhenius equation. The amidation mechanism for forming the "chemical N" and "lattice N" at an atomic level was also proposed. Linearly controlling the optical band-gap with the ALN cycle number was suggested as a robust method for tuning the oxidation as well as the amidation level on the GO sheets. In this sense, nitrogen functionalization can be utilized for engineering any desirable properties within the graphene sheets.